Renaissance of the vaginal microbiota: reframing clinical paradigms - G.N. Minkina; K.R. Bondarenko; М.S. Selikhova; P.A. Soltys (LCC «Medicine-Inform», 2022)
G.N. Minkina1, K.R. Bondarenko2, M.S. Selikhova3, P.A. Soltys3 1A.I. Yevdokimov Moscow State University of Medicine and Dentistry, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation 3Volgograd State Medical University, Volgograd, Russian Federation One of the promising options for reducing the prevalence of inflammatory diseases of the genital organs and preventing their recurrence is to achieve and maintain a normal vaginal microbiome as the first line of natural protection against infections. Medications comprising antibacterial and/or antifungal agents which are widely used in the treatment of abnormal vaginal discharges may cause a substantial decrease in woman's own lactobacilli. Over the last decade, researchers have focused on probiotics which increase the efficacy of treatment and reduce the rate of disease recurrences. As known, the human gut microbiota plays a central role in the development of healthy microbiome of its host and biotopes of various locations. Thus, the currently preferred oral probiotics include combination products for oral intake which contain multiple symbiont bacterial strains and prebiotic components. An oral probiotic comprising a combination of two lactic acid bacteria wi th synergistic effect, Lactobacillus rhamnosus HN001 and Lactobacillus acidophilus La-14 that remain viable after passing through the gastrointestinal tract and maintain ability to colonize the vagina as well as other organs and are characterized by a high level of adhesion to vaginal epithelial cells, helps to increase the lactobacilli count, normalizing microbiome in the woman's vagina. The recent clinical trials have demonstrated the efficacy of oral administration of the combination of two strains of lactic acid bacteria, L. rhamnosus HN001 and L. acidophilus La-14, in the prevention of recurrences of bacterial vaginosis and vulvovaginal candidiasis with the aim of maintaining and normalizing vaginal microbiome; this combination is approved for taking during pregnancy and breastfeeding. Keywords: vaginal infections, microbiome, probiotics, oral intake, symbiont bacterial strains, normal vaginal biocenosis. For citation: Minkina G.N., Bondarenko K.R., Selikhova M.S., Soltys P.A. Renaissance of the vaginal microbiota: reframing clinical paradigms. Russian Journal of Woman and Child Health. 2022;5(4):303-308 (in Russ.). DOI: 10.32364/2618-8430-2022-5-4-303-308.